The influence of stance width on movement time in field hockey goalkeeping - Ball, K.; Giblin, G. (ISBS - Conference Proceedings Archive (Konstanz), 2009)
Minimising movement time is essential for a field hockey goalkeeper and stance width is considered important to agility. The aim of this study was to examine if an optimal stance width exists for field hockey goalkeepers and if so, does it vary for different movement directions and for different individuals. Ten state and national level goalkeepers made simulated saves from ten different stance widths ranging from 0.4 m to 1.2 m. AMTI force plate data was used to identify start of movement time and timing gates in the corner of the goals recorded the end of movement time. On a group basis, a stance width of 1.1 m was optimal for minimising movement time for high and low saves and for right and left saves. On an individual basis, 1.1 m was the optimal stance for eight of ten subjects. Only two subjects performed optimally at their preferred stance width. Where shots to the corner of the goals are likely, goalkeepers should adopt a wide stance.